Portfolio Analysis of Financial Institutions in Nepal - Pandeya, Churamani; Shrestha, Santosh (The Harvest, 2024)
In this paper we empirically investigated risk return dynamics of the financial institutions that were selected from the Nepal Stock Exchange for the period of 2016-2022. The objective of this study is to analyze the portfolio of different FIs based on the return and risk parameters using ex-post returns data. This study employed financial and statistical tools to draw the conclusion. The beta values show that commercial banks’ share prices are more volatile than the prices of development banks and finance companies. The alpha coefficients reveal that share prices of all commercial banks and development banks are found overvalued and couple of finance companies is undervalued. The results of correlation coefficient offer a scope of diversification in the Nepalese stock market.